The Development of Taman Sari Waterfall as A Spiritual-Based Natural Tourist Attraction in Banjar Adat Ngenjung Sari, Bakbakan Village, Gianyar District - Wayan Gede Palguna (Nawasena: Jurnal Ilmiah Pariwisata, 2025)
The tourism industry in Bali has experienced rapid growth over time. This study focuses on the development of Taman Sari Waterfall as a spiritual-based natural tourist attraction in Banjar Adat Ngenjung Sari, Bakbakan Village, Gianyar District. The research addresses the following problems: (1) What is the potential of Taman Sari Waterfall as a spiritual-based natural tourist attraction in Banjar Adat Ngenjung Sari, Bakbakan Village, Gianyar District? (2) How is Taman Sari Waterfall marketed as a spiritual-based natural tourist attraction? (3) What development strategies are applied to enhance Taman Sari Waterfall as a spiritual-based natural tourist attraction?. This research employs a qualitative approach using purposive sampling. Data were collected through observation, interviews, literature study, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings of the study include: (1) The potential of Taman Sari Waterfall as a spiritual-based natural tourist attraction is analyzed using the 4A framework: Attraction, Amenity, Accessibility, and Ancillary services; (2) The marketing approach is based on the 4P analysis: Product, Price, Place, and Promotion; (3) The development strategy utilizes a SWOT analysis encompassing Strengths, Weaknesses, Opportunities, and Threats.